Sex determination studies in two species of teleost fish, Oreochromis niloticus and Leporinus elongatus - Baroiller, Jean-François; Nakayama, Ichiro; Foresti, Fausto [UNESP]; Chourrout, Daniel (My University, 1996)
Genetic analyses of sex determination have identified sex chromosomes in many teleost fish species. However, there are several cases for which sex ratios do not fit perfectly with the expectations of heterogametic systems, suggesting the influence of either minor sex determining genes or environmental influences on the process of sex differentiation. The frequent absence of sex chromosome markers makes the identification of minor sex-determining genes very difficult. It is easier to test first the hypothesis of environmental sex determination (ESD) by studying the temperature effect, since temperature-dependent sex determination has been demonstrated to occur in several vertebrate groups including 1 fish species. To contribute to a better understanding of fish sex determination, we have tested the effects of high temperatures on sex ratios of Oreochromis niloticus, and have attempted to isolate sex chromosome molecular markers in Leporinus elongatus. Treatments of O. niloticus fry at 36°C applied for 10 days and more, and starting 1 week after fertilization markedly increased the proportion of males, and progeny-testing these males confirmed that some of them are sex-reversed genetic females. Two non-coding sequences of L. elongatus Z and W chromosomes were cloned by genomic subtraction. They cross-hybridized with the genome of a close species without providing sex-specific patterns. A collection of L. elongatus individuals was subjected to gonadal and chromosomal sexing, and DNA hybridization with both sequences. These analyses revealed 3 individuals having atypical W chromosomes. Interestingly, 2 of these were males having a ZW karyotype. We assume that these atypical sex chromosome arise by exchanges between Z and W chromosomes, and that a transition between female and male heterogamety is underway in this species.
Keywords: Fish; Genetics; Leporinus; Oreochromis; Sex determination